A new species of Tisis Walker from North Sumatra, Indonesia (Lepidoptera: Lecithoceridae) - Heppner, John B.; Park, Kyu-Tek; Bae, Yang-Seop (Zootaxa, 2021)
A new species of the genus Tisis Walker is described from Sumatra, Indonesia, which is very close to T. sumatraensis Park, 2007.